Management Problems in Socio-Economic Systems: Theory, Methodology, Practice - Litvinov A. N., Smirnova I. L., Baranova N. A., Iovleva O. O., Mishulina O. V., Malanina A. A., Mfliarenko O. I., Panina G. V., Gorelova N. S., Lilimberg S. I., Kulakova S. V., Borovkova V. A., Borovkova V. A., Kul'chikova Z. T. (Management Problems in Socio-Economic Systems: Theory, Methodology, Practice, 2019)
this article examines the problems of formation and subsequent management of economic security of the subjects of the agricultural sector of the economy (on the example of the existing agricultural enterprise LLP «ABC»). The study was conducted using analytical, statistical, graphical methods, as well as the method of situational analysis. The result of the study was the development and updating of a step-by-step model of formation and management of the system of economic security of agricultural producers. The application of this model will allow, firstly, to identify the main threats that damage the efficiency of economic entities; secondly, to take timely measures to neutralize threats.
Keywords: экономическая безопасность; угроза; economic security; управление рисками; risk management; идентификация угроз; управление экономической безопасностью; threat; threat identification; economic security management